1989
DOI: 10.1111/j.1600-0536.1989.tb04658.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoses in metal workers

Abstract: In an epidemiological study of 286 metalworkers exposed to metalworking fluids (MWF), the prevalence of skin problems was investigated. Minor changes, such as a dry rough skin with slight erythema, were seen in 31%, and major changes, such as more serious and widespread dermatitis, were observed in 27% of all workers. By far the most cases were of irritant origin; in only 2.8% was a contact sensitization established. Exposure to water-based MWF caused irritant contact dermatitis more often than exposure to nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…Recent patch test results obtained from the medical surveillance of great numbers of workers (de Boer et al, 1989;Goh and Ho, 1993) or patients (Kanerva et al, 1997; were all negative.…”
Section: Hypersensitivity Allergy and Intolerancementioning
confidence: 99%
“…Recent patch test results obtained from the medical surveillance of great numbers of workers (de Boer et al, 1989;Goh and Ho, 1993) or patients (Kanerva et al, 1997; were all negative.…”
Section: Hypersensitivity Allergy and Intolerancementioning
confidence: 99%
“…A clearly positive result obtained in 1/24 control persons was thought to be caused by excessive use of an anti-dandruff shampoo containing zinc pyrithione (De Boer et al 1989). Patch tests carried out on 230 metal industry workers with dermatitis on their hands or forearms revealed no reactions to a 1 % aqueous solution of sodium pyrithione (Alomar et al 1985).…”
Section: Allergenic Effectsmentioning
confidence: 98%
“…It was reported that there were about 27% of metalworkers affected by several dermatitis and extensive response to repeated contact with MWFs. 19 In another study, Sprince et al 20 showed that there was a prevalence of contact dermatitis of about 27.2% among 158 machine operators in the automotive production sector. Mirabelli et al 21 conducted a study on the effect of MWFs on persistent skin symptoms based on survey data from ECRHS II (European Community Respiratory Health Survey II) and SAPALDIA 2 (Swiss Cohort Study one Air Pollution and Lung and Heart Diasease in Adults 2).…”
Section: Introductionmentioning
confidence: 97%